Increasing students' mood state and self-confidence: 3 weeks plywood bow pvc archery program - Muzakki, Abdurrohman; Arifin, Bustanol; Saputra, Setiya Yunus; Setiawan, Edi; Gani, Ruslan Abdul; NÃ©meth, Zsolt (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
The decline in the psychological aspect between the mood state and student self-confidence in the COVID-19 era became a gap in this research. The purpose of this research is try to increasing of two psychological aspects between students' self-confidence and mood state through learning archery with PVC plywood bows. The research method used was experimental and as many as 70 students from Universitas Muhammadiyah Malang were prepared to be subjects in this research. Data analysis used the IBM SPSS version 25.0 application to test descriptive statistics, normality and homogeneity of data and paired sample t-test to determine the increase in mood state and self-confidence state before and after the intervention program. The level of significance chosen was .05. The results of the research found that archery learning with PVC plywood bows had a significant positive effect on increasing two psychological aspects, namely students' mood state and self-confidence. Thus, this research concludes that eventhough there are many obstacles in the learning conditions in the COVID-19 era, then learning archery with PVC plywood bows has been proven to increase of students' mood state and self-confidence for the better.